miR-940 is a new biomarker with tumor diagnostic and prognostic value - Hongxiang Li; Yin Li; Dongmei Tian; Jiaqian Zhang; Shiwei Duan (Molecular Therapy: Nucleic Acids, 2021)
miR-940 is a microRNA located on chromosome 16p13.3, which has varying degrees of expression imbalance in many diseases. It binds to the 3′ untranslated region (UTR) and affects the transcription or post-transcriptional regulation of target protein-coding genes. For a diversity of cellular processes, including cell proliferation, migration, invasion, apoptosis, epithelial-to-mesenchymal transition (EMT), cell cycle, and osteogenic differentiation, miR-940 can affect them not only by regulating protein-coding genes but also long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) in pathways. Intriguingly, miR-940 participates in four pathways that affect cancer development, including the Wnt/β-catenin pathway, mitogen-activated protein kinase (MAPK) pathway, PD-1 pathway, and phosphatidylinositol 3-kinase (PI3K)-Akt pathway. Importantly, the expression of miR-940 is intimately correlated with the diagnosis and prognosis of tumor patients, as well as to the efficacy of tumor chemotherapy drugs. In conclusion, our main purpose is to outline the expression of miR-940 in various diseases and the molecular biological and cytological functions of target genes in order to reveal its potential diagnostic and prognostic value as well as its predictive value of drug efficacy.